Dibenzohexacene: Stabilization Through Additional Clar Sextets. Issue 5 (2nd November 2017) - Rüdiger, Elias C.; Müller, Matthias; Koser, Silke; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: Triphenylene units stabilize hexacenes as dibenzohexacenes. The hexacenes formed by a statistical Yamamoto coupling of dibromobenzene with dibromo‐TIPS‐pentacene or, alternatively, Stille coupling with dimethyldibenzostannole. UV/Vis spectroscopy and quantum chemical calculations show that despite the double benzannulation, the species have hexacene‐type character, as evidenced by their redshifted absorption characteristics. The charge carrier mobility of dibenzohexacene1 a was determined up to 0.2 cm 2 /(Vs). Abstract : Stabilized : Adding Clar Sextets to the end stabilizes a hexacene.